A Vision-Based Method for Autonomous Landing of a Rotor-Craft Unmanned Aerial Vehicle. Issue 3 (8th July 2010) - Yuan, Z.; Gong, Z.; Chen, J.; Wu, J.
Abstract : This article introduces a real-time vision-based method for guided autonomous landing of a rotor-craft unmanned aerial vehicle. In the process of designing the pattern of landing target, we have fully considered how to make this easier for simplified identification and calibration. A linear algorithm was also applied using a three-dimensional structure estimation in real time. In addition, multiple-view vision technology is utilized to calibrate intrinsic parameters of camera online, so calibration prior to flight is unnecessary and the focus of camera can be changed freely in flight, thus upgrading the flexibility and practicality of the method.